2014
DOI: 10.31254/phyto.2014.3109
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany, phytochemistry, pharmacology and toxicology profiles of Cassia siamea Lam.

Abstract: Cassia siamea is a shrub belonging to the Fabaceae family, native of Southeast Asia and better known in folklore medicine, feeding, agriculture and manifacture all over the world including Côte d’Ivoire. C. siamea has recently been shown to have antimicrobial, antimalarial, antidiabetic, anticancer, hypotensive, diuretic, antioxidant, laxative, anti-inflammatory, analgesic, antipyretic, anxiolytic, antidepressant, and sedative activities. Chromone (anhydrobarakol), Chromone alkaloids (barakol, cassiarin A-B), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 95 publications
0
20
0
1
Order By: Relevance
“…Its different parts have been utilized by people in various ways, both medicinally and in daily life in Asia . Its leaves are used as vegetables by the natives of Thailand …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its different parts have been utilized by people in various ways, both medicinally and in daily life in Asia . Its leaves are used as vegetables by the natives of Thailand …”
Section: Introductionmentioning
confidence: 99%
“…Concerning the synthesis of Ag NPs from the recent literature, it was found that most studies have been performed using leaf extracts. ,, Only a few were pertained to flower extracts . The effects of various surfactants on the shape and size of Ag NPs have been studied using both plant and chemical reducing agents. , However, regarding plant extract-mediated synthesis, mostly cationic surfactants have been used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Southeastern and Sub-Saharan parts of Africa, the root decoction is used for the treatment of diabetes mellitus, amongst other ailments. Scientific studies have revealed that S. siamea has recently been shown to have antimicrobial, anti-malarial, anti-diabetic, anti-cancer, hypotensive, diuretic, antioxidant, laxative, anti-inflammatory, analgesic, antipyretic, anxiolytic, antidepressant, and sedative activities (Kamagaté et al, 2014).…”
Section: Introductionmentioning
confidence: 99%